Pre-testing of the WHO’s Educational Video: “How to Protect Yourself Against COVID-19” - Fadliyah, Hilyatul; Muhtar, Manendra; Munih, Munih; Risgiantini, Sylviasari; Wulandary, Weny; Pratomo, Hadi (UI Scholars Hub, 2020)
The coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was declared a public health emergency in many countries, including Indonesia. The World Health Organization (WHO) released an educational video, entitled